Influence of Drying Rate on Hot Air Drying Processing of Fresh Foods Using Pulsed Electric Field. Issue 7 (13th May 2020) - Yamada, Takahiro; Yamakage, Kouya; Takahashi, Katsuyuki; Takaki, Koichi; Orikasa, Takahiro; Kamagata, Junichi; Aoki, Hitoshi
Abstract : Influence of pulsed electric field (PEF) on the drying rate of foods during the hot air drying process is investigated. Nine kinds of fruits and vegetables and two kinds of marine products are used as the samples, and changes in the weight of these samples during the process are evaluated. PEF is applied to the samples using parallel plate electrodes. The applied voltage ranges from 0.4 to 3 kV, and the input energy of the sample ranges from 1.5 to 115.5 J/g. The samples are dehydrated using a hot air dryer after the PEF treatment. The drying rate of leafy vegetables, apples, and wakame seaweed is accelerated by PEF. The results show that the moisture permeability of membrane can be improved by destroying the cell membrane by PEF. On the other hand, there is no effect on root vegetables because their hard tissues are hard to destroy. © 2020 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.